RANCANG BANGUN SISTEM INFORMASI PEMESANAN TIKET TRAVEL BERBASIS WEBSITE MENGGUNAKAN METODE EXTREME PROGRAMMING (STUDI KASUS: FAJRI JAYA TRAVEL) - Sansabila, Rosa; Albar, Moh. Ali; Aranta, Arik (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2025)
Fajri Jaya Travel is a transportation service provider based in West Nusa Tenggara. In conducting its business activities, the company still uses the manual method, where prospective passengers are required to either visit the ticket agent in person or contact them by phone to book tickets or inquire about schedules, ticket prices, or seat availability. This method is inefficient and time-consuming, especially for people living far from ticket agents or having difficulties accessing information quickly. Furthermore, this approach is susceptible to recording errors, such as incorrect passenger data or duplicate seat numbers. To address this issue, this study aims to develop an online ticket booking system for Fajri Jaya Travel. This system will allow prospective passengers to obtain departure schedules and book tickets through a website, without the need to visit a ticket agent in person and minimizing data entry errors. This system is built using the Bootstrap and Laravel frameworks with the Extreme Programming development method. The system was tested using Black Box Testing to assess functionality and the Mean Opinion Score method to evaluate user satisfaction, resulting in average scores of 4.4 from administrators, 4.0 from drivers, and 4.55 from general users, indicating a high level of satisfaction.